Recent Advances in Stereoselective Chemical O-Glycosylation Reactions - Mukherjee, Mana Mohan; Ghosh, Rina; Hanover, John A. (Frontiers in Molecular Biosciences, 2022)
Carbohydrates involving glycoconjugates play pivotal role in many life processes. Towards better understanding of glycobiological events including the structure-function relationship of these biomolecules and for diagnostic and therapeutic purposes including tailor-made vaccine development, synthesis of structurally well-defined oligosaccharides (OS) becomes important. Efficient chemical glycosylation in high yield and stereoselectivity is however challenging and depends on the fine tuning of protection profile to get matching glycosyl donor-acceptor reactivity along with proper use of other important external factors like catalyst, solvent, temperature, activator, additive, etc. So far, many glycosylation methods have been reported including several reviews also. In the present review we will concentrate our discussion on the recent trend on α- and β-selective glycosylation reactions reported during the past decade.